Coexistence of giant cell arteritis and subacute thyroiditis: A case report and literature review - Cheng Xu; Yongmei Han (Journal of International Medical Research)
Giant cell arteritis and subacute thyroiditis are often regarded as clinically distinct diseases with differing pathogenesis. We report a rare case of coexisting giant cell arteritis and subacute thyroiditis that were both successfully managed using glucocorticoid therapy. Ultrasound plays a vital role in the diagnosis and treatment of these diseases. A review of the literature revealed that cases of giant cell arteritis complicated by subacute thyroiditis are very rare, and their pathogenesis and association are still unclear. We summarized the clinical features of giant cell arteritis complicated with subacute thyroiditis and found that none of the patients had symptoms associated with polymyalgia rheumatica. Subacute thyroiditis could be misdiagnosed as giant cell arteritis, and ultrasound is a useful tool for distinguishing the two diseases. Glucocorticoids are effective in the active period in patients with giant cell arteritis complicated with subacute thyroiditis. This case report would encourage clinicians to pay more attention to this phenomenon.